Expression of Vascular Endothelial Growth Factor and Interleukin-6 in bile duct healing with autologous parietal peritoneum: a non-inferiority experimental study in rabbits - Anung Noto Nugroho; Soetrisno Soetrisno; Ambar Mudigdo; Kristanto Yuli Yarso; Dono Indarto; Akmal Zhahir Wahyudi (PeerJ)
Background Bile duct injury (BDI) remains a serious complication of hepatobiliary surgery, particularly in laparoscopic cholecystectomy, often leading to strictures, fibrosis, and long-term morbidity. Although traditional repair techniques such as primary suturing and Roux-en-Y hepaticojejunostomy are widely used, they carry risks of anastomotic complications and bile duct dysfunction. Autologous peritoneum has emerged as a potential alternative graft material due to its biocompatibility and regenerative properties. This study evaluates the efficacy of autologous parietal peritoneum graft in bile duct healing, focusing on fibroblast activity, vascular endothelial growth factor (VEGF), and interleukin-6 (IL-6) expression as indicators of tissue remodeling. Materials and Methods This experimental study involved 27 male New Zealand rabbits (Oryctolagus cuniculus), divided into three groups: group A (primary bile duct closure), group B (gallbladder transplant), and group C (parietal peritoneum transplant). The rabbits were anesthetized using a combination of ketamine, xylazine, isoflurane, and sevoflurane. Postoperative care included antibiotics and pain management. The study employed a post-test-only design. IL-6 and VEGF expression were assessed using enzyme-linked immunosorbent assay (ELISA), and the anastomosis was pathologically evaluated using hematoxylin and eosin (H&E) staining. Statistical analysis was conducted with SPSS 28.0, using one-way analysis of variance (ANOVA) or Kruskal–Wallis tests, with significance set at p < 0.05. Ethical approval was obtained. Results On day 3, fibroblast infiltration was significantly lower in the autologous peritoneum group (p = 0.040) compared to other groups, suggesting delayed initial recruitment. By day 7, fibroblast density increased, and by day 14, all groups exhibited well-organized tissue structures with no significant intergroup differences. VEGF (p = 0.788 on day 3, 0.473 on day 7, and 0.586 on day 14) and IL-6 (p = 0.629 on day 3, 0.587 on day 7, and 0.925 on day 14) levels showed no significant variations among the groups, indicating comparable angiogenic and inflammatory responses across treatment conditions. Conclusion Autologous peritoneum supports gradual bile duct healing, despite initial delayed fibroblast recruitment, with histological evidence of progressive tissue remodeling. However, the lack of significant differences in VEGF and IL-6 levels suggests that angiogenesis and inflammation were similarly regulated across groups. Given the study’s short follow-up period, further research is needed to assess the long-term integration, functional outcomes, and potential benefits of autologous peritoneum in bile duct reconstruction.